A Viscoelastic Model of Ice Stream Flow with Application to Stick-Slip Motion - Walker, Ryan T.; Parizek, Byron R.; Alley, Richard B.; Nowicki, Sophie M. J. (Frontiers in Earth Science, 2016)
Stick-slip motion such as that observed at Whillans Ice Stream, West Antarctica, is one example of transient forcing significantly affecting longer-term ice-stream dynamics. We develop and present a two-dimensional map-plane viscoelastic model of perturbations to ice-stream dynamics suitable for simulating and analyzing stick-slip behavior. Model results suggest important roles in stick-slip motion for both the elastic and viscous components of ice rheology, confirming and extending inferences drawn from simple models and observations. Elastic behavior depends on the rate of applied stress, at times allowing significant velocity perturbations with little change in accumulated stress perturbation; in contrast, viscous behavior depends on total accumulated stress and can lead to changes in ice-stream thickness over many stick-slip cycles.